2013
DOI: 10.1111/bph.12137
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of histamine H4 receptor agonists in triple‐negative human breast cancer experimental model

Abstract: BACKGROUND AND PURPOSEThe presence of the histamine H4 receptor (H4R) was previously reported in benign and malignant lesions and cell lines derived from the human mammary gland. The aim of this work was to evaluate the effects of H4R ligands on the survival, tumour growth rate and metastatic capacity of breast cancer in an experimental model. EXPERIMENTAL APPROACHXenograft tumours of the highly invasive human breast cancer cell line MDA-MB-231 were established in immune deficient nude mice. The following H4R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 40 publications
8
53
0
Order By: Relevance
“…Finally, in this study, we assessed the short-term effect of clozapine (over 2 to 3 days), but not the long-term effect. Although the dose of clozapine that we used was rational and has been implemented in many studies [22,42,43], we also demonstrated that even at a lower concentration, clozapine continued to impair NSCLC cell growth during treatment for a longer period. Not only is this finding consistent with the clinical observation that patients with schizophrenia require prolonged antipsychotic administration [24], but the dose that we used for long-term treatment was also closer to the actual dose used in the clinic [44,45].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, in this study, we assessed the short-term effect of clozapine (over 2 to 3 days), but not the long-term effect. Although the dose of clozapine that we used was rational and has been implemented in many studies [22,42,43], we also demonstrated that even at a lower concentration, clozapine continued to impair NSCLC cell growth during treatment for a longer period. Not only is this finding consistent with the clinical observation that patients with schizophrenia require prolonged antipsychotic administration [24], but the dose that we used for long-term treatment was also closer to the actual dose used in the clinic [44,45].…”
Section: Discussionmentioning
confidence: 92%
“…In vitro studies using liquid culture systems and immunofluorocytometry have revealed that clozapine specifically exhibits toxic effects against myeloid maturation [21]. However, only few studies have been conducted to study the drug's potential anticancer effects [22], and the possible mechanisms underlying the induction of autophagy have not been explored. In the present study, we hypothesized that clozapine could inhibit the proliferation of NSCLC cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have recently reported that in vivo H 4 R ligands' administration produced a significant decrease in tumor growth rate in a triple negative breast cancer experimental model. 16 Interestingly, histamine was able to potentiate in vivo the anti-tumoral effect of gamma radiation, increasing the exponential tumor doubling time, suggesting that histamine could also be investigated as a potential adjuvant to cancer radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors of MDA-MB-231 cells were developed as previously described. 16 When the tumor volumes reached 8 mm in diameter (on day 22 after surgery) xenografted mice were separated into 3 groups, the Untreated group received a subcutaneous (sc) daily injection of saline solution (n D 6), Untreated 2 Gy group received a sc daily injection of saline solution (untreated and irradiated animals, n D 6) or Histamine 2 Gy group received a sc daily injection of histamine 5 mg/kg (treated and irradiated, n D 6). One day after treatment began, animals were irradiated with a 2 Gy dose per day for 3 consecutive days.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation